Interaction effects of sleep duration and activities of daily living on depressive symptoms among Chinese middle-aged and older adult individuals: evidence from the CHARLS - Tianmeng Wang; Wenjin Han; Caihua Wang; Yanqing Kang; Yaping Wang; Shuangyan Lei; Zhaozhao Hui; Ning Li; Xiaoqin Wang; Xiaoqin Wang (Frontiers in Public Health, 2025)
ObjectivesEvidence on the combined effect of sleep duration and activities of daily living (ADL) on depressive symptoms is scarce. This study aimed to explore the interaction effects between sleep duration and ADL limitations on depressive symptoms among Chinese individuals aged ≥45 years.MethodsData were extracted from the China Health and Retirement Longitudinal Study (CHARLS) wave 2020. Sleep duration was self-reported. The Center for Epidemiological Studies Depression Scale and a 12-item scale were employed to estimate depressive symptoms and ADL limitations, respectively. Logistic regression analysis was conducted to examine the interaction effects between sleep duration and ADL limitations on depressive symptoms.ResultsLogistic regression found that short sleep (OR = 1.69, 95% CI: 1.57–1.83), long sleep (OR = 0.87, 95% CI: 0.79–0.95), and ADL limitations [basic activities of daily living (BADL), OR = 1.82, 95% CI: 1.66–2.01; instrumental activities of daily living (IADL), OR = 1.88, 95% CI: 1.71–2.07] were associated with depressive symptoms. Furthermore, synergistic interaction effects on the depressive symptoms risk were identified between short sleep and IADL limitations (RERI = 1.08, 95% CI: 0.57–1.59) or BADL limitations (RERI = 1.13, 95% CI: 0.60–1.65). Conversely, antagonistic interaction effects were observed between long sleep and IADL limitations (RERI = 0.88, 95% CI: 0.39–1.38) or BADL limitations (RERI = 0.76, 95% CI: 0.25–1.27) on depressive symptoms.ConclusionThe study revealed significant interactions between sleep duration and ADL limitations on depressive symptoms, suggesting that enhancing ADL’s function and ensuring adequate sleep duration could effectively prevent depressive symptoms.